Nox4-SH3YL1 complex is involved in diabetic nephropathy - Sae Rom Lee; Hye Eun Lee; Jung-Yeon Yoo; Eun Jung An; Soo-Jin Song; Ki-Hwan Han; Dae Ryong Cha; Yun Soo Bae (iScience, 2024)
Summary: Nox4-derived H2O2 generation plays an important role in the pathogenesis of chronic kidney diseases (CKDs) such as diabetic nephropathy (DN). Here, we showed that SH3 domain-containing Ysc84-like 1 (SH3YL1), a Nox4 cytosolic activator, regulated DN. Streptozotocin (STZ)-induced type Ⅰ diabetic models in SH3YL1 whole-body knockout (KO) mice and podocyte-specific SH3YL1 conditional KO (Nphs2-Cre/SH3YL1fl/fl) mice were established to investigate the function of SH3YL1 in DN. The expression of fibrosis markers and inflammatory cytokines, the generation of oxidative stress, and the loss of podocytes were suppressed in diabetic SH3YL1 KO and Nphs2-Cre/SH3YL1fl/fl mice, compared to diabetic control mice. To extrapolate the observations derived from diabetic mice to clinical implication, we measured the protein level of SH3YL1 in patients DN. In fact, the SH3YL1 level was increased in patients DN. Overall, the SH3YL1-Nox4 complex was identified to play an important role in renal inflammation and fibrosis, resulting in the development of DN.